Double Trouble: A Rare Case of Concurrent Biliary Adenofibroma and Hepatobiliary Mucinous Cystic Neoplasm. Issue 1 (2018) - Esteban, Marcus; Amin, Jaimin; Hertl, Martin; Jakate, Shriram; Singh, Ajaypal
ABSTRACT : N/A: Biliary adenofibroma and hepatobiliary mucinous cystic neoplasm are exceedingly rare tumors. To our knowledge, no case of co‐existent biliary adenofibroma and mucinous cystic neoplasm has been previously reported. We present a patient who was diagnosed with both tumors concurrently. Both can present with abdominal pain, although some are diagnosed incidentally in asymptomatic patients. Imaging and tumor markers can be suggestive, but histologic examination is needed for definitive diagnosis. Both have a propensity for malignant transformation, thus complete surgical resection is the treatment of choice. Although rare, awareness of these tumors leads to earlier diagnosis and treatment.